The effect of product innovation towards brand image and its implication on consumer buying behavior (a case of Toshiba television in Jakarta) - Jesslyn Octavia; A.B.M. Witono; Dedi Kurniawan (International Journal of Family Business Practices, 2021)
The television production industry is facing fierce competition from its substitutes such as the smartphone industry. Television manufacturers need to find the right strategy to maintain sales. This study aims to examine the effect of product innovation on brand image and consumer buying behavior on television products. Research on product innovation and its contribution to brand image and consumer buying behavior specifically in the television production industry is not yet fully observed. This study used quantitative methods with survey techniques. Toshiba television product is the object of the research. Three hundred respondents who had purchased television responded to a questionnaire distributed in the DKI Jakarta area, Indonesia. Data were analyzed using the Structural Equation Modeling technique by employing AMOS software. The study found that product innovation has a significant effect on brand image and consumer buying behavior. Brand image also has a significant effect on consumer buying behavior. Hence, product innovation and brand image are both important factors that can influence consumer buying behavior. These two aspects should be the main concern for television manufacturers, especially Toshiba, to compete grabbing consumers.